Role of eosinophils and apoptosis in PDIMs/PGLs deficient mycobacterium elimination in adult zebrafish. (June 2016) - Huang, Xinhua; Wang, Hui; Meng, Lu; Wang, Qinglan; Yu, Jia; Gao, Qian; Wang, Decheng
Abstract: The cell wall lipids phthiocerol dimycocerosates (PDIMs) and its structurally-related compound, phenolic glycolipids (PGLs) are major virulence factors of mycobacterium, as shown by the reduced growth of PDIMs/PGLs deficient mutants in various animal models. PDIMs/PGLs play active roles in modulating host immune responses. However, the cellular and molecular mechanisms of how PDIMs/PGLs deficient mutant was eliminated in vivo are still elusive. Our aim was to investigate what host immune responses have effect on mycobacterium elimination in vivo. Using microarray, we find PDIMs/PGLs modulate divergent host responses, including chemotaxis and focal adhesion's downstream pathway and apoptosis. We examine these two host responses by Diff-Quik stain, coupled with transmission electron microscopy and TUNEL stain respectively. The ultrastructure observation showed that eosinophils appeared in WT-infected zebrafish at day 1, however eosinophils arrived was delayed to day 7 in PDIMs/PGLs-deficient mutant-infected animals. More intriguingly, apoptosis was markedly increased in PDIMs/PGLs-mutant infected zebrafish at day 1 after infection, compared to WT-infected fishes at this time. However, apoptosis trend was fully reversed by day 7, with increased apoptosis were detected in WT-infected zebrafish compared with the PDIMs/PGLs-deficient mutant, especially more apoptosis within the granuloma. This study shows that the anti-apoptotic effects of PDIMs/PGLs and the recruitment of eosinophils in tissue during the early infection in zebrafish might promote bacterium growth in vivo. Highlights: This is the first time of a host transcriptional study with WT and PDIMs/PGLs deficient infection at the organismal level. PDIMs/PGLs-deficient mutant of M. marinum delayed tissue eosinophil recruitment. PDIMs/PGLs inhibit early apoptosis. Role of eosinophils and apoptosis in PDIMs/PGLs deficient mutant elimination is suggested.